2019
DOI: 10.3390/cryst9050228
|View full text |Cite
|
Sign up to set email alerts
|

The Photorefractive Response of Zn and Mo Codoped LiNbO3 in the Visible Region

Abstract: We mainly investigated the effect of the valence state of photorefractive resistant elements on the photorefractive properties of codoped crystals, taking the Zn and Mo codoped LiNbO3 (LN:Mo,Zn) crystal as an example. Especially, the response time and photorefractive sensitivity of 7.2 mol% Zn and 0.5 mol% Mo codoped with LiNbO3 (LN:Mo,Zn7.2) crystal are 0.65 s and 4.35 cm/J at 442 nm, respectively. The photorefractive properties of the LN:Mo,Zn crystal are similar to the Mg and Mo codoped LiNbO3 crystal, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Hexavalent dopants: Mo 6+ is predicted to dope at the niobium site, with charge compensation by lithium vacancy formation. The occupation of the niobium site is supported by experimental data [16,17,19].…”
Section: Hexavalent Dopantsmentioning
confidence: 70%
See 1 more Smart Citation
“…Hexavalent dopants: Mo 6+ is predicted to dope at the niobium site, with charge compensation by lithium vacancy formation. The occupation of the niobium site is supported by experimental data [16,17,19].…”
Section: Hexavalent Dopantsmentioning
confidence: 70%
“…Another study looks at LiNbO 3 co-doped with Mg and V, concluding that some of the vanadium dopes at the Nb site in the 5+ charge state, but that V 4+ Li , V 3+ Li and V 2+ Li defects are also observed [18]. Finally, another recent publication [19] has looked at the photorefractive response of Zn and Mo co-doped LiNbO 3 in the visible region, and concluded that the presence of Mo 6+ ions helps promote fast response and multi-wavelength holographic storage, which is attributed to their occupation of regular niobium sites in the lattice.…”
Section: Introductionmentioning
confidence: 98%
“…It's worth noting that the Mo element exhibited three valence states in the KCMP crystal, in which the combined peaks of 236.29 eV and 233.14 eV represent +6 valence, and the insignificant peaks at 234.18 eV and 232.01 eV represent +5 and +4 valence, respectively. 42 Moreover, the characteristic peaks of O 1s were 530.74 eV and 532.35 eV, corresponding to the coordinated oxygen and chemisorbed oxygen, respectively. 40…”
Section: Resultsmentioning
confidence: 98%
“…S1a (ESI†), indicating that the grown KCMP crystal was of high purity. The binding energy (BE), relative content, and valence state of each component element in the KCMP crystal were analysed by referring to the relevant literature reports, 40–43 and the results are listed in Table S1(ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The photorefractive properties of lithium niobate (LN): Mo,Zn crystals with different doping concentrations were investigated in paper [1]. Zinc can shorten the response time and improve the photorefractive sensitivity of the LN:Mo,Zn crystal.…”
Section: Photorefractive Properties and Defect Structurementioning
confidence: 99%